Development and Validation of a Risk Score in Chinese Patients With Chronic Heart Failure - Lin, Maoning; Zhan, Jiachen; Luan, Yi; Li, Duanbin; Shan, Yu; Xu, Tian; Fu, Guosheng; Zhang, Wenbin; Wang, Min (Frontiers in Cardiovascular Medicine, 2022)
Background: Acute exacerbation of chronic heart failure contributes to substantial increases in major adverse cardiovascular events (MACE). The study developed a risk score to evaluate the severity of heart failure which was related to the risk of MACE. Methods: This single-center retrospective observational study included 5,777 patients with heart failure. A credible random split-sample method was used to divide data into training and validation dataset (split ratio = 0.7:0.3). Least absolute shrinkage and selection operator (Lasso) logistic regression was applied to select predictors and develop the risk score to predict the severity category of heart failure. Receiver operating characteristic(ROC) curves, and calibration curves were used to assess model’s discrimination and accuracy. Results: Body-mass index(BMI), ejection fraction(EF), serum creatinine, hemoglobin, C-reactive protein(CRP), and neutrophil lymphocyte ratio(NLR) were identified as predictors and assembled into the risk score(P<0.05), which showed good discrimination with AUC in training dataset (0.770, 95% CI: 0.746–0.794) and validation dataset (0.756, 95% CI: 0.717–0.795) and was well calibrated in both datasets (all P>0.05). As the severity of heart failure worsened according to risk score, the incidence of MACE, length of hospital stay and treatment cost increased(P<0.001). Conclusion: A risk score incorporating BMI, EF, serum creatinine, hemoglobin, CRP, and NLR, was developed and validated. It effectively evaluated individuals’ severity classification of heart failure, closely related to MACE.